Comparative Analysis of Informal Vendors around Dhaka Metro Stations through a Sustainable Livelihood Framework - Rizwana, Syeda; Rahman, Tahmina; Shawpnil, S M Ehsan Ul Haque (Journal of Contemporary Urban Affairs, 2025)
Dhaka’s urban landscape is undergoing rapid transformation with the introduction of the Metro Rail, reshaping mobility patterns and influencing informal economies. This study investigates how the establishment of Farmgate and Mirpur-10 metro stations has affected the livelihoods of informal vendors, applying the Sustainable Livelihood Framework (SLF) as an analytical lens. A mixed-method research design was adopted, combining structured questionnaires, semi-structured interviews, field observations, and photographic documentation with statistical analyses. Fifty vendors were surveyed across the two sites, and independent sample t-tests were performed to compare livelihood outcomes. Results indicate that vendors who relocated their vending spaces after the opening of metro stations achieved significantly higher SLF scores (p < .01), reflecting improved access to financial and social capital. In contrast, vendors who started business after the metro inauguration reported comparatively lower livelihood scores, suggesting vulnerabilities linked to competition, limited infrastructure, and regulatory constraints. Findings underscore the dual role of transport infrastructure as both an enabler of opportunity and a source of precarity for informal workers. The study highlights the necessity of inclusive urban policies, particularly through designated vending zones and supportive planning strategies, to enhance resilience and ensure equitable benefits from infrastructure-led urban transformation.